Peningkatan Kesiapsiagaan Bencana Pada Anak Tunagrahita Ringan Menggunakan “Pop Up Book For Disability (Pobody) Di SLB Negeri 1 Padang” - Arif Rohman Mansur; Ira Mulya Sari; Yelly Herien; Deswita Deswita; Kintan Resqitha; Serly Berlian; Rahtu Susi Amelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
West Sumatra area is the most prone to earthquakes; that disaster is an event that cannot be avoided and occurs suddenly, so sometimes it causes many fatalities. Children with disabilities are vulnerable to becoming victims of disasters, and this is due to the understanding. Lack of preparedness for children dealing with disasters. Pop-Up Book for Disability (POBODY) is an educational book for children with disabilities, especially developmentally disabled people. It displays an overview of disaster preparedness in the form of pop-up pictures. The problem that has been agreed with partners is the lack of understanding of students with mild mental retardation categories about disaster preparedness and the need for partners. Students can understand disaster conditions and prepare themselves if a disaster occurs according to their abilities. For this reason, the community services team conducted education in SLB Negeri 1 Padang. The team conducted preparedness for children with disabilities, exceptionally mild developmentally disabled children with an age range of 6-12 years, using the POBODY. This book is an educative storybook on disaster preparedness for children with disabilities consists of 11 pages. The team's before and after education with disaster preparedness with the POBODY can increase preparedness for earthquake disasters in children with mild mental retardation.